iHeatCup / Amal Hanani Zikri ... [et al.] - Zikri, Amal Hanani; Noor Hisham, Nur Annisa; Mat Asli, Reem; Washi, Syazwani; Zulkurnain, Syazwani Najwa (2021)
iHeatCup instant noodle is the latest specialty of our company with application of push- heat- button (PHB) technology. Push-heat-button technology is a new technology developed by iHeatCup Sdn. Bhd. that has never been applied on other instant noodles. PHB technology uses exothermic chemical reaction to heat and cook food inside the packaging without external heating or electricity. This instant noodle with PHB technology allows people to enjoy the noodle anytime with less effort required.Product produced by our company, iHeatCup Sdn. Bhd. will comply to the fundamental principle of the business which is to give convenience to the consumer. Target market of iHeatCup product are students, workers, family, travellers and hikers. iHeatCup allows these people to have more time for work as they can reduce their time and effort to prepare a meal as well as allow them to have their meal at places without heating sources. This product can help to solve travellers’ problem to find food to eat especially traveller who travel abroad.iHeatCup instant noodle is created to bring the convenience of self- heating instant food to another level. Other self-heating instant foods use a separate heating pad to heat the food. As for iHeatCup product, the application of PHB technology allows heating of food without separate heating pad which is the competitive advantage among other self- heating product. PHB is a two-chambered plastic which one for food and for the heating unit. This technology has a heating module inside it which helps to cook the food from the heat produces by the exothermic chemical reaction activated by pushing the activator button on the bottom of the cup. As we are the only producer with this technology, this strengthens our value and remain competitive to other self- heating product producers.